Urbanization and (In)Formalization - Ghani, Ejaz (World Bank, Washington, DC, 2014)
Inexorable urbanization and formalization have been the expectations in development discourse. Indeed, measures of urbanization and formalization have been provided and used as indicators of development. But while urbanization has proceeded apace in developing countries, formalization has slowed significantly over the past quarter century. These disconnect raises questions for development analysis and development policy. Why did one expect urbanization and formalization to go together in the first place? Is the link between urbanization and formalization more complex than what had once thought? What then explains the recent disconnect between urbanization and formalization? Is formalization a reasonable policy goal? May urbanization policies and formalization policies conflict? If so, what can be done to resolve the conflicts? These are the questions this paper addresses. The paper has three core sections. The first section asks what exactly is meant by formality and informality. The second section turns to urbanization processes and asks how they intersect with and interact with the incentives to formalize. The third section looks at policy. Each view of how urbanization feeds formalization has distinctive policy conclusions.